Digital transformation and its implications for professional accountants' skills needs - Sintadevi, Ni Putu Rita; Suarta, I Made; Swintana, I Ketut (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Digital transformation brings significant changes to clerical accounting tasks. This research aims to (1) investigate digital technology that has a broad impact on the field of accounting; and (2) identify the skills needed by accounting graduates to enter the workforce in the digital era. The research was conducted with a qualitative approach using a systematic literature review method. In the initial phase, this study identified 40 manuscripts. Based on the selection criteria, this study examined 26 manuscripts about digital transformation related to the skills needs of the accounting profession. Manuscripts come from 21 journals indexed by Scopus Q1 – Q3 and published in the period 2019 – 2024. Digital technologies such as big data and data analytics, artificial intelligence, robotic process automation, blockchain, and cloud-based accounting are having a broad impact on accounting processes and practices. The implications of this impact are the changing role of the accounting profession. A number of new skills, both technical and non-technical, are needed to support the changing role of the accounting profession. Therefore, educational institutions need to prepare accounting graduates with a range of skills, supported by digital skills. Further studies are needed to identify patterns of changes in the role of the accounting profession and its skills requirements.